Coastal Environment, Disaster, and Infrastructure A Case Study of China's Coastline - San Liang, X.; Zhang, Yuanzhi (IntechOpen, 2018)
The coastal environment is deteriorating at an alarming rate and is currently a great societal concern. This book provides a selected collection of papers on coastal environmental change, coastal disasters, and coastal infrastructure due to global warming, with a focus on the coasts of the rapidly developing country China. What makes the book distinctly different from others is its diversity, reflecting the interdisciplinary nature of coastal problems. With contributions from over 30 authors, the book is a comprehensive account of diverse topics, such as coastal upwelling, estuarine processes, coastal pollution, sea level rise, meteorological and atmospheric problems, urbanization and the heat island effect, and coastal infrastructure, to name just a few, from theoretical study and phenomenological description, to methodological development. This book is expected to serve as a relatively comprehensive reference for coastal researchers, graduate students, as well as policymakers and coastal resource managers.